Portfolio Performance and the Investment Horizon - Levy, Haim (Management Science, 1972)
Following the equilibrium model which has been developed by Sharpe, Lintner and Treynor, several authors have developed one-parameter indexes as measures of performance. In this paper, it is shown that as long as the “true” horizon does not coincide with the horizon assumed in the empirical research, the one-parameter indexes contain a systematic bias, even when one assumes a perfect market. In conducting empirical research or in evaluating the performance of the management of a portfolio, more attention should be devoted to the selection of the investment horizon, since the magnitude as well as the direction of the systematic bias is a function of this factor.